Neonates with Covid-19 infection: Is there any different treatment process? - Manizhe Pakdel; Nasim Pouralizadeh; Raheleh Faramarzi; Hassan Boskabadi; Gholamali Mamouri (Elsevier, 2022)
This study was designed to investigate the neonates with COVID-19 admitted to two hospitals in Neyshabur and Mashhad, Iran. In this study, 17 neonates are introduced with positive nasopharyngeal COVID-19 polymerase chain reaction (PCR) test who admitted to two hospitals in Iran. Perinatal information, contacts with a person with COVID-19 infection, clinical signs at the time of admission, laboratory tests, radiological evaluations, pulmonary and extra pulmonary complications, and short-term outcome have been reported. 8 neonates had positive COVID-19 PCR test of mothers at the time of delivery in the first 24 hours and subjected to invasive or non-invasive mechanical ventilation due to respiratory distress. 9 neonates on 9-18 days of birth were admitted with pulmonary and extra pulmonary symptoms by fever as a main clinical sign. All of cases except one had a history of contact with the infected person. The treatments were mostly supportive, by the way 6 neonates receiving surfactant treatment and 2 of them receiving systemic steroid therapy. Only one neonate died and the others were discharged without any complications. The results showed that the symptoms and severity of the disease in neonates are milder than adults. The possibility of vertical transmission due to the onset of symptoms immediately after birth is still present in some neonates of affected mothers.